Liver lipopolysaccharide binding protein prevents hepatic inflammation in physiological and pathological non-obesogenic conditions. (January 2023) - Milbank, Edward; Díaz-Trelles, Ramon; Dragano, Nathalia; Latorre, Jèssica; Mukthavaram, Rajesh; Mayneris-Perxachs, Jordi; Ortega, Francisco; Federici, Massimo; Burcelin, Remy; Karmali, Priya P.; Tachikawa, Kiyoshi; Chivukula, Pad; et al.
Abstract: Lipopolysaccharide binding protein (LBP) knockout mice models are protected against the deleterious effects of major acute inflammation but its possible physiological role has been less well studied. We aimed to evaluate the impact of liver LBP downregulation (using nanoparticles containing siRNA- Lbp) on liver steatosis, inflammation and fibrosis during a standard chow diet (STD), and in pathological non-obesogenic conditions, under a methionine and choline deficient diet (MCD, 5 weeks). Under STD, liver Lbp gene knockdown led to a significant increase in gene expression markers of liver inflammation ( Itgax, Tlr4, Ccr2, Ccl2 and Tnf ), liver injury ( Krt18 and Crp ), fibrosis ( Col4a1, Col1a2 and Tgfb1 ), endoplasmic reticulum (ER) stress ( Atf6, Hspa5 and Eif2ak3 ) and protein carbonyl levels. As expected, the MCD increased hepatocyte vacuolation, liver inflammation and fibrosis markers, also increasing liver Lbp mRNA. In this model, liver Lbp gene knockdown resulted in a pronounced worsening of the markers of liver inflammation (also including CD68 and MPO activity), fibrosis, ER stress and protein carbonyl levels, all indicative of non-alcoholic steatohepatitis (NASH) progression. At cellular level, Lbp gene knockdown also increased expression of the proinflammatory mediators ( Il6, Ccl2 ), and markers of fibrosis ( Col1a1, Tgfb1 ) and protein carbonyl levels. In agreement with these findings, liver LBP mRNA in humans positively correlated with markers of liver damage (circulating hsCRP, ALT activity, liver CRP and KRT18 gene expression), and with a network of genes involved in liver inflammation, innate and adaptive immune system, endoplasmic reticulum stress and neutrophil degranulation (all with q-value<0.05). In conclusion, current findings suggest that a significant downregulation in liver LBP levels promotes liver oxidative stress and inflammation, aggravating NASH progression, in physiological and pathological non-obesogenic conditions. Graphical Abstract: ga1